DUALISME IDEOLOGI DALAM IDENTITAS SPIRITUAL KOMUNITAS BHUJANGGA DI BALI - Wisnu, I Wayan Gede (Universitas Wijaya Kusuma Surabaya, 2023)
This paper presents a critical study of ideological aspects of identity in the spirituality of society as reflected through phenomena in the realm of the Bhujangga community in Bali. In this case, the spiritual identity of the community identifies a dualism related to the legitimacy of the Vaishnava ideology through the formal institutional authority of kinship, which tends to be contradictory to the inheritance of a number of Siwaistic markers such as being verified and affiliated with the Bhujangga ideology. In line with this phenomenon, this study focuses on a discussion of constructivity and correlativity related to ideological dualism in the spiritual identity of the Bhujangga community. This study was conducted through descriptive and interpretive methods based on a number of concepts from the semiotic theory of cultural interpretation by Geertz and critical discourse theory by Foucault. The results of this study indicate that the constructivity of ideological dualism in the spiritual identity of the Bhujangga community is related to (1) cognitive identity and (2) collective identity. Meanwhile, the correlativity of ideological dualism in the spiritual identity of the Bhujangga community is related to (1) the domination of the Vaishnava ideology and (2) the degradation of the Bhujangga ideology.Keyword: Vaishnava ideology, Bhujangga ideology, Bhujangga community